Dynamic Capabilities in Halal Skincare Product Development: A Case Study of Startup Indonesia - Valentino Raja Hasibuan; Arien Arianti Gunawan (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The halal skincare industry in Indonesia has experienced significant growth along with increasing consumer awareness of product safety, quality, and religious values. However, the highly dynamic market environment requires firms to develop strong adaptive capabilities to remain competitive. This study aims to analyze the implementation of dynamic capabilities, consisting of sensing, seizing, and reconfiguring, in the development of halal skincare products at JGlow as a local startup. A qualitative descriptive approach was employed, with data collected through in-depth interviews, observation, and documentation. The findings reveal that JGlow effectively identifies market opportunities through emerging halal and clean beauty trends, integrates key resources such as halal and BPOM certification, medical professionals, and formulation technology during the seizing stage, and continuously renews its human resources, production systems, and product innovation in the reconfiguring stage. These results indicate that JGlow’s competitive advantage is not solely derived from halal compliance but also from its ability to systematically manage and adapt to environmental changes. The study concludes that dynamic capabilities play a crucial role in enhancing innovation and ensuring the sustainability of halal skincare businesses. The implication suggests that local cosmetic firms should strengthen adaptive capabilities to improve competitiveness in an increasingly competitive market.